2014
DOI: 10.2971/jeos.2014.14008
|View full text |Cite
|
Sign up to set email alerts
|

Interferometric out-of-focus imaging simulator for irregular rough particles

Abstract: We present the development of an original simulator to predict interferometric out-of-focus patterns created by irregular rough particles. Despite important simplifications of the scattering properties, this simulator allows to predict quantitative properties of the speckle-like patterns: i.e. the dimension of the central peak of the 2D-autocorrelation of the pattern. This parameter can then be linked to the size and the shape of the particle projected on the CCD sensor, in cases where there is no exact theore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(21 citation statements)
references
References 24 publications
(35 reference statements)
1
20
0
Order By: Relevance
“…Its coefficients depend on the coefficients of the optical transfer matrix describing the optical elements encountered between the particle and the sensor. The procedure has been detailed in references [12,17] in the case of droplets represented by a pair of Dirac emitters, and has been validated in all cases that could be tested experimentally [7,8,12,17]. We obtain the following expression of the electric field in the plane of the CCD sensor [12]:…”
Section: Theoretical Formulationmentioning
confidence: 99%
See 3 more Smart Citations
“…Its coefficients depend on the coefficients of the optical transfer matrix describing the optical elements encountered between the particle and the sensor. The procedure has been detailed in references [12,17] in the case of droplets represented by a pair of Dirac emitters, and has been validated in all cases that could be tested experimentally [7,8,12,17]. We obtain the following expression of the electric field in the plane of the CCD sensor [12]:…”
Section: Theoretical Formulationmentioning
confidence: 99%
“…It is then possible to evaluate the expression of the electric field in the plane of the CCD sensor. According to reference [12], and neglecting the role of the aperture of the imaging system (big aperture), the electric field can be evaluated in the plane of the CCD sensor from a generalized Huygens Fresnel integral [17]. Its coefficients depend on the coefficients of the optical transfer matrix describing the optical elements encountered between the particle and the sensor.…”
Section: Theoretical Formulationmentioning
confidence: 99%
See 2 more Smart Citations
“…In the case of irregular rough particles such as ice crystals, the out-of-focus image shows a speckle-like pattern. The size of the droplet is deduced from the frequency of the fringes, while size and ellipticity of irregular particles are deduced from size and ellipticity of the speck of light in the speckle pattern [40]. In this last case, it can be demonstrated that the 2-Dimensional Fourier transform of the speckle pattern gives the 2-Dimensional autocorrelation of the global shape of the object [41].…”
Section: Library Of Ice Crystal Objects For the Calibration Of Interfmentioning
confidence: 99%